Pharmacokinetics, tissue distribution, and antitumor activity of a novel compound, NY-2, in non-small cell lung cancer - Zhang, Yingshi; Xu, Chang; Xu, Xiangbo; Ma, Lingxiang; Li, Ruolan; Xu, Zihua; Zhao, Qingchun (Frontiers in Pharmacology, 2023)
ZLDI-8, an inhibitor of ADAM-17 which has a relatively strong anti-tumor activity and acts on the Notch pathway. To further optimize its structure and improve activity, a series of derivatives are synthesized. NY-2, which is the most effective derivative of ZLDI-8 from preliminary activity screening in vitro, with no obvious under administration in vivo. The study aimed to further evaluate the pharmacokinetics, tissue hepatotoxicity and nephrotoxicity distribution and anti-tumor activity on Non-small Cell Lung Cancer (NSCLC) of compound NY-2 in vitro and in vivo. The pharmacokinetics parameters of NY-2 were better than ZLDI-8 in vivo experiments. Meanwhile, the tissue distribution research found that tail vein injection of 6 mg/kg NY-2 obtained the highest concentration in the lung in rats, so we speculated that NY-2 might target the treatment of NSCLC. Besides, NY-2 could significantly inhibit colony formation, invasion and migration, and increase LDH activity and cell apoptosis in a concentration-dependent manner in NSCLC cells. Moreover, tail vein injection of 6 mg/kg NY-2 also inhibited the formation of lung metastases without significant toxicity to major organs in nude mice. In conclusion, compared with parent compound ZLDI-8, the activity and safety of compound NY-2 were improved, NY-2, which could be a potential anti-tumor agent, could organize the occurrence and development of NSCLC which targeted Notch1 and Integrinβ1 signally pathway.